Intervenção educativa para promoção da autoeficácia de pais e/ou cuidadores no manejo e controle da asma infantil: ensaio clínico randomizado - Mendes, Elizamar Regina da Rocha (2022)
Hospitalizations and deaths from asthma in children are due to lack of disease control. Therefore, it is necessary that parents and/or caregivers have knowledge and feel capable of carrying out the proper management of the disease. Educational interventions that use educational technologies based on the theory of self-efficacy associated with motivational interviewing can help parents/caregivers to control their children's asthma. The objective was to evaluate the effect of an educational intervention using a booklet associated with a brief motivational interview (MBE) on the self-efficacy of parents and/or caregivers of children in the management and control of childhood asthma. This is a Randomized Clinical Trial developed in two Primary Health Care Units (UAPS) in Fortaleza, with 84 parents and/or caregivers of children under five years of age, divided into two groups: Intervention Group (GI), who received an educational intervention using a booklet associated with EMB; and the Comparison Group (GC), which received conventional care from the UAPS. Data collection took place in two phases, the first at the UAPS with the application of the Self-Efficacy and Their Child's Level of Asthma Control Scale: Brazilian version (STCLA –VB) and the sociodemographic form, with GI and GC; then at the UAPS itself, the educational intervention was carried out with a booklet and EMB with the GI. The second phase took place by telephone with the application of the STCLA-VB scale and the asthma symptoms investigation form with IG and GC, with an interval of 15 days and after one month of the educational intervention at the UAPS. The groups were compared at baseline and one month after the intervention, using the chi square test, Fisher-Freeman-Halton and Student's t test. The project was approved by the Research Ethics Committee of the Universidade Federal do Ceará and by the Brazilian Registry of Clinical Trials. The groups were homogeneous at baseline. After the intervention, the mean self-efficacy scores of the IG were always higher than those of the CG. Evidencing a statistically significant difference between the Intervention Group and the Comparison Group for the total scale scores (p<0.0001), efficacy expectations (p<0.0001) and outcome expectation domain (p<0.0001) . There was an increase in high self-efficacy scores in the IG from the 1st to the 2nd evaluation with statistical significance (p<0.0001). It was found that the comparison group was more likely to have nocturnal symptoms (OR=3.0; p=0.019) and to visit the emergency room due to asthma (OR=30.75; p<0.0001). There was a greater predominance of participants with high self efficacy in the IG after the educational intervention. Children of parents and/or caregivers in the CG were 1.43 times more likely to have asthma attacks than children in the IG. It is concluded that the educational intervention proposed from the reading of the booklet based on the concept of self-efficacy and associated with EMB was able to raise the self efficacy scores of parents and/or caregivers in the control and management of childhood asthma and less chance of their children have asthma attacks.